Gagea bohemica in Slovakia : 1. Taxonomy and Distribution - Košťál, Jaroslav; Eliáš jun, Pavol; Vojteková, Helena; Dítě, Daniel (Hacquetia, 2015)
Distribution, morphological types and coenotic affinity of Gagea bohemica in Slovakia was studied during 2008–2011. Revision of herbarium material showed presence of three taxa in the flora: 1) subsp. bohemica, 2) subsp. bohemica var. stenochlamydea and 3) subsp. saxatilis. Taxonomic status of var. stenochlamydea is uncertain and requires further research. In total, 42 localities of G. bohemica sensu lato were documented. Nominate subsp. bohemica (including var. stenochlamydea) predominated and it was recently confirmed at 21 localities. These current sites represent about 50% of all known sites, therefore we re-assessed the status of G. bohemica in the Slovak Red List and we proposed the IUCN category EN (endangered) for this taxon. Subsp. saxatilis was found as new to Slovakia. The taxon occurred only at single locality (Vinosady) and it was not confirmed recently. We assessed it as data deficient (DD).